Toll-like receptors-2 and -9 (TLR2 and TLR9) gene polymorphism in patients with type 2 diabetes and diabetic foot - Wifi, Mohamed-Naguib Abdalla; Assem, Maha; Elsherif, Rasha Hamed; El-Azab, Hameda Abdel-Fattah; Saif, Aasem (Medicine (Baltimore), 2017)
Toll-like receptors (TLRs) are innate immune receptors that mediate the inflammatory response in diabetes mellitus (DM). The aim of this study is to evaluate the association of TLR2 and TLR9 gene polymorphism in patients with type 2 DM (T2DM) and diabetic foot (DF).The study included 90 subjects divided into group I (30 patients with T2DM and DF), group II (30 patients with T2DM and no evidence of DF), and group III (normal control subjects). TLR2 (1350 T/C, rs3804100) and TLR9 (1237 T/C, rs5743836) genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique for all subjects.There was a statistically significant difference in the distribution of TLR9-1237 T/C genotypes between groups I and II (P < .029) as well as between groups I and III (P < .001). Calculated risk estimation revealed that TLR9-1237 polymorphism conferred almost 20 times increased risk of DF disorders in T2DM (OR = 20, 95% CI = 5.38-74.30). There was no statistical difference in the distribution of TLR2-1350T/C genotypes between the 3 groups.TLR9-1237 T/C gene polymorphism may be considered as a molecular risk for DF among patients with T2DM.